Intracardiac Metastases Detected by 18F-FSPG PET/CT. (January 2018) - Magarik, Meaghan A.; Walker, Ronald C.; Gilbert, Jill; Manning, H. Charles; Massion, Pierre P.
Abstract : Abstract: PET/CT imaging is frequently used for cancer diagnosis and restaging as metabolically active cells, including cancer, utilize glucose for proliferation. 18 F-FDG is the most commonly utilized radiopharmaceutical in PET/CT imaging. Limitations of 18 F-FDG imaging include intense physiologic uptake in benign tissues such as the brain and myocardium. We present a case of non–small cell lung cancer with myocardial and pericardial metastases obscured by physiologic 18 F-FDG cardiac uptake but detected with the investigational PET radiotracer (4S)-4-(3- 18 F-fluoropropyl)-L-glutamate ( 18 F-FSPG), which targets a pathway associated with glutathione biosynthesis. This case demonstrates the added value of 18 F-FSPG PET/CT imaging.